What causes spasm of atherosclerotic arteries? Is regression of plaques beneficial? - Heistad, D. D. (American Clinical and Climatological Association, 1990)
We would like to emphasize three points. First, atherosclerosis produces a profound alteration of vascular responses, which may lead to spasm in several vascular beds. Second, we have proposed that leukocytes as well as platelets may play a critical role in the pathophysiology of vasospasm. Third, there is bad news and good news in relation to regression of atherosclerosis. Maximal vasodilator capacity does not improve consistently during regression of atherosclerosis, but endothelium-dependent relaxation improves, hypersensitivity of blood vessels subsides, and we speculate that susceptibility to vasospasm may be abolished.